Tobacco Use Decreases Visual Sensitivity in Schizophrenia - Fernandes, Thiago M. P.; Andrade, Michael J. Oliveira de; Santana, Jessica B.; Nogueira, Renata M. Toscano Barreto Lyra; Santos, Natanael A. dos (Frontiers in Psychology, 2018)
Smoking prevalence in patients who are diagnosed with schizophrenia (SCZ) is higher than in the general population. Chronic tobacco use in SCZ patients may reduce the side effects of antipsychotic drugs, thus serving as a self-medication for such side effects. Understanding the ways in which chronic tobacco use influences visual sensitivity has clinical implications, which may serve as a tool for non-invasively diagnosing early-stage visual processing deficits. The present study evaluated the effects of chronic tobacco use on visual sensitivity in SCZ patients. Our purpose was to provide new directions for future research, mainly psychophysical and electrophysiological studies. In the present study, 40 smoker controls (SC), 20 SCZ tobacco users, and 20 SCZ tobacco nonusers were recruited from the Psychosocial Care Center. Visual sensitivity was compared between both SCZ groups and the SC group. Patients with SCZ who were chronic tobacco users presented lower visual sensitivity for chromatic (p < 0.001) and achromatic (p < 0.001) stimuli compared with the other groups. Our findings highlight the need to evaluate possible addictive behavior in patients with SCZ, which may contribute to public policies that seek to improve the quality of life of SCZ patients and their families.